Bad people - Petrovitch, Alex; Markwood Films (Firm); Leomark Studios (Firm) ([Los Angeles, California] : Markwood Films, 2016)
Sketch comedy is back! If "Key & Peele" & "Clerks" had sex, BAD PEOPLE would be their deranged child! A quirky & smart dark comedy, bursting with sex, violence, dirty politics & fame whores, BAD PEOPLE is a hilarious tale that reminds us that we all have a dark side! This soon-to-be cult classic slashes our corrupt society with several dark & nasty short stories jam packed with silly & whacky characters! Sex-starved surfer girls seeking random guys online, crack addicted politicians, reality TV whores, religious scam artists, and more! BAD PEOPLE will have you pissing your pants for years to come! --
Originally released as a motion picture in 2016
Euriamis Losada, Andy Mackenzie, Justin Shipley, Ben Gleib, Anne Girard, Jeneta St. Clair, Chris Goodman, Rosalind Rubin, Nate Weisband, Sita Young, Leah McKendrick, Sara Fletcher, Brad Fletcher.
Editor, Alex Petrovitch.
In English; with optional English subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed January 25, 2018)
Keywords: Comedy films; Feature films; Internet videos; Streaming video